2019
DOI: 10.1021/acssynbio.9b00191
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering of an Aspirin-Responsive Transcriptional Regulator in Escherichia coli

Abstract: Bacterial transcription factors (TFs) are key devices for the engineering of complex circuits in many biotechnological applications, yet there are few well-characterized inducer-responsive TFs that could be used in the context of an animal or human host. We have deciphered the inducer recognition mechanism of two AraC/XylS regulators from Pseudomonas putida (BenR and XylS) for creating a novel expression system responsive to acetyl salicylate (i.e., aspirin). Using protein homology modeling and molecular docki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…The mutation A111V was previously found to change the induction specificity of XylS. 46 Thus, the influence of residue 111 was investigated here by performing site-directed saturation mutagenesis. After screening, XylS variants A111C, A111L, A111V, and A111F showed clear fluorescence response to 5 mM PA and TPA (Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The mutation A111V was previously found to change the induction specificity of XylS. 46 Thus, the influence of residue 111 was investigated here by performing site-directed saturation mutagenesis. After screening, XylS variants A111C, A111L, A111V, and A111F showed clear fluorescence response to 5 mM PA and TPA (Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The unpredictable behaviors observed in these studies might also depict a deeper evolutionary trend in gene regulation that has selected molecular systems/mechanisms capable of promoting both evolvability and robustness of gene expression levels through non-linear gene regulation (Steinacher et al, 2016). Thus, understanding the way the architecture of cis-regulatory elements determines gene expression behavior is pivotal not only to understand natural bacterial systems but also to provide novel conceptual frameworks for the construction of synthetic promoters for biotechnological applications (Monteiro et al, 2019b). Frequently, in genetic bioengineering applications, it is also necessary to fine-tune and balance specific gene expression due to the complexity of regulatory networks (Boyle and Silver, 2012;Scalcinati et al, 2012;Steinacher et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…molecular docking studies with sensors and site-directed mutagenesis, Silva-Rocha et al engineered new transcription factors with enhanced responses to certain molecules, like benzoate and salicylic acid, for eliciting gene expression in E. coli. 18 In another study, Fields and colleagues recently reported on the generation of Saccharomyces cerevisiae digoxigenin and progesterone biosensors based on destabilized dimeric ligand-binding domains that undergo ligand-induced stabilization. 19 These biosensors will increase the flexibility for the construction of logic gates and other potential applications in the future.…”
Section: Engineering Sensor Proteinsmentioning
confidence: 99%
“…For example, bacterial transcription factors play essential roles in the engineering of complex biological circuits. Using molecular docking studies with sensors and site-directed mutagenesis, Silva-Rocha et al engineered new transcription factors with enhanced responses to certain molecules, like benzoate and salicylic acid, for eliciting gene expression in E. coli . In another study, Fields and colleagues recently reported on the generation of Saccharomyces cerevisiae digoxigenin and progesterone biosensors based on destabilized dimeric ligand-binding domains that undergo ligand-induced stabilization .…”
mentioning
confidence: 99%